Awareness of AIDS among STD clinic attenders in the Cape Peninsula - Blecher, Mark S (Department of Paediatrics and Child Health, 2017)
This descriptive study aimed to determine the knowledge, attitudes and practices about AIDS among Sexually Transmitted Disease (STD} clinic attenders in the Cape Peninsula. A questionnaire containing open and closed questions in the appropriate language (English, Afrikaans or Xhosa) was administered by trained clinic staff to 306 patients in 9 of the 29 STD Clinics in the region. The study was requested by the local authorities to initiate and improve AIDS education programmes within the STD clinics. 306 patients were interviewed in 9 clinics. The median age of attenders was 25 years. The median period of residence in the peninsula was 7 years. Knowledge of AIDS is reasonably good when tested by true/false questions but much worse when tested by open questions. Knowledge bears little relationship to practice. There is inadequate awareness of the asymptomatic carrier state, the incurability of AIDS and ways to prevent AIDS. Sexual practice is high risk. Condom use is extremely low especially in the African areas where only 9,6% used a condom in the past year. Prostitution is perceived to be a common occurrence in attenders' communities. There is a low perception of risk to self. The most important beliefs militating against condom use are that they are unacceptable to partners and peer group. More information about AIDS was requested by 90% of patients and a strong preference was expressed for programmes to be conducted in the patient's home language. This study supports the urgent need for an AIDS education and counselling programmes for patients with STD's in the region. Recommendations include the need to address the emotions, attitudes and beliefs that affect behaviour as well as to convey knowledge. Condom acceptability poses a major problem that will need to be addressed. Patients with STDs represent an extremely important core group for HIV transmission to others in the community and need specific attention and resources.